2002
DOI: 10.1515/bc.2002.120
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Placental Proteases

Abstract: The placenta is a critical organ in mammals required for the transport of nutrients from the mother to the fetus during gestation. Other critical functions of the placenta include hormone regulation and immune regulation. The origin of the mammals and early placenta is relatively recent in evolutionary terms, and consequently there are few placenta-specific genes. In two separate branches of mammalian evolution, gene duplications have given rise to two large families of protease genes that are expressed only b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, the extent of inhibition of invasion by cystatin M observed in the present study, that is, X95%, suggested that cystatin M may target some cysteine protease(s) that was rate-limiting in the proteolytic cascade, leading to matrix dissolution and invasion. The potential physiological target(s) of cystatin M could be one of the 11 papain-type cysteine proteases (Bromme and Kaleta, 2002;Mason et al, 2002;Puente et al, 2003), or it could be a legumain-type cysteine protease such as Asn-endopeptidase (Alvarez-Fernandez et al, 1999). With a K i of 1.6 pM, cystatin M indeed very efficiently inhibits Asn-endopeptidase ( ¼ mammalian legumain) (Alvarez-Fernandez et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, the extent of inhibition of invasion by cystatin M observed in the present study, that is, X95%, suggested that cystatin M may target some cysteine protease(s) that was rate-limiting in the proteolytic cascade, leading to matrix dissolution and invasion. The potential physiological target(s) of cystatin M could be one of the 11 papain-type cysteine proteases (Bromme and Kaleta, 2002;Mason et al, 2002;Puente et al, 2003), or it could be a legumain-type cysteine protease such as Asn-endopeptidase (Alvarez-Fernandez et al, 1999). With a K i of 1.6 pM, cystatin M indeed very efficiently inhibits Asn-endopeptidase ( ¼ mammalian legumain) (Alvarez-Fernandez et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the closely related Cathepsin L, which is found in a broad variety of eukaryotic species and is ubiquitously expressed, the PECs are expressed only in the placenta and are found only in rodents (for review, see Mason et al 2002). Of the Cathepsins in our mature placenta cluster, J/P, M, Q, and R are found in both rats and mice, while 3 and 6 are believed to exist in mice alone (Deussing et al 2002; for reviews, see Mason et al 2002;Sol-Church et al 2002).…”
Section: Duplicated and Diverged Rodent Specific Placental Gene Familiesmentioning
confidence: 99%
“…In contrast to the closely related Cathepsin L, which is found in a broad variety of eukaryotic species and is ubiquitously expressed, the PECs are expressed only in the placenta and are found only in rodents (for review, see Mason et al 2002). Of the Cathepsins in our mature placenta cluster, J/P, M, Q, and R are found in both rats and mice, while 3 and 6 are believed to exist in mice alone (Deussing et al 2002; for reviews, see Mason et al 2002;Sol-Church et al 2002). The PECs are cysteine proteases that are believed to have arisen via gene duplication, then evolved to have greater substrate specificity compared with the related Cathepsins L and K. Based on their exclusive expression in the placenta, it has been suggested that PECs may contribute to embryonic nutrition or may have evolved to more efficiently process conserved or novel placental hormones and proteins (for review, see Mason et al 2002).…”
Section: Duplicated and Diverged Rodent Specific Placental Gene Familiesmentioning
confidence: 99%
See 2 more Smart Citations